(untitled) (Praxis Educativa, 2025)
This study aims to describe and analyze the digital practices of primary school teachers, considering the different social and cultural conditions that frame them. Based on a qualitative case study focused on public primary schools located in the south of the Province of Santa Fe (Argentina) and drawing on ethnographic approaches, various tensions permeating the relationship between technology and education in the studied contexts were identified. The results highlight a diverse and heterogeneous set of digital teaching practices that persist despite the lack of policies, adequate technological resources, or updated training. These practices take place thanks to the effort and dedication of teachers who, despite adversity, integrate digital tools into their classrooms. The study emphasizes the need to reflect on the challenges of the current post-digital landscape and the role of digital technologies in educational contexts.